Tunable single- and dual-wavelength lasers around 1.4 μm in Nd:LuGdAG crystal - Haotian Huang; Yuzhao Li; Nguyen Tuan Anh; Yanfei Lü; Jing Xia (PLoS ONE, 2025)
We present the first diode-pumped tunable single- and dual-wavelength (DW) laser operation near 1.4 μm spectral region in Nd:LuGdAG (Nd:LGAG) crystal on the 4F3/2 → 4I13/2 transition. Three distinct lasing wavelengths at 1414 nm, 1426 nm and 1437 nm were generated by adjusting a Lyot filter (LF) in the cavity, respectively. The maximum continuous-wave (CW) power output of 3.64 W at 1414 nm was attained under an absorbed pump power of 18.7 W, exhibiting a slope efficiency of 23.7% and optical conversion efficiency of 19.5%. Further, three pairs of DW lasers operating at 1414 nm and 1426 nm, 1414 nm and 1437 nm, 1426 nm and 1437 nm were also achieved, respectively. The DW operation at 1414 nm and 1437 nm yielded 2.82 W total CW output power, attaining 15.1% total optical conversion efficiency. Single- and DW lasers in the 1410–1440 nm spectral range have important application in fields such as optical communication and medicine.